Popularizing makhana cultivation in water garden - Pan, T K; Pandit, N (Indian Horticulture, 2019)
Makhana has high demand in national and international market. It is needs to be cultivated in more areas to fulfil its demand. So, it is recommended that makhana can be grown in cemented tank in water garden for beautification, conservation and food items. Apart from its high nutritive value, it is equally important medicinally. The seeds of makhana are used in Ayurveda for the treatment of chronic diarrhoea, vaginal discharges, kidney weakness associated with frequent urination, impotency, premature ejaculation, nocturnal emissions and strengthening the heart.